METABOLIC CHANGES IN MUSTARD DUE TO ALTERNARIA LEAF BLIGHT - C. D. KAUSHIK, S. K. GUPTA, P. P. GUPTA, T. P. YADAVA AND (Indian Phytopathology, 2002)
The levels of total phenols and specific activities of polyphenol oxidase (PPO), peroxidase (PO), and catalase in the leaves of Alternaria blight (Alternaria brassicae and A. brassicicola) tolerant (RC-781, RH-8113) and-susceptible (RH-30, Prakash) cultivars of mustard were determined at 20 days interval after 40 days of sowing. Total phenols increased initially and then decreased with the age of plant. These were markedly higher in tolerant cultivars as compared to susceptible ones at all the stages of plant development. After infection their amount decreased in all the genotypes. The specific activities of polyphenol oxidase remained higher while that of peroxidase was lower in tolerant cultivars in comparison to susceptible. In response to infectjon, the activity of both the enzymes increased sharply in all the cultivars. However, this increase was considerably higher in susceptible cultivars than that of tolerant. Catalase activity was appreciably higher at initial stage, at later stages it dropped markedly. In response to infection, its activity decreased. The role of phenolics and oxidative enzymes in determining resistance in mustard against Alternaria blight disease has been highlighted.